Fatal pulmonary hemorrhage after taking anticoagulation medication - Samuel P. Hammar (Respiratory Medicine Case Reports, 2015)
We describe a 64-year-old man with extensive diffuse acute lung hemorrhage, presumably as a result of anticoagulation therapy. We evaluated reports in the literature concerning acute exacerbation (acute lung injury of unknown cause) in UIP and other forms of fibrotic interstitial pneumonias. We also evaluated autopsy tissue in this case in order to determine the cause of death in this 64-year-old man, who was initially thought to have an asbestos-related disease. Based on the autopsy findings, this man died as a result of anticoagulation therapy; specifically, the use of Xarelto® (rivaroxaban).